DEVELOPMENT OF A WORKING CURRICULUM FOR PHARMACEUTICAL CHEMISTRY FOR STUDENTS-PHARMASISTS AT PROFESSIONAL COLLEGE - Velyka, Alla; Garvasiuk, Oleksandra (SWorldJournal, 2025)
This article is dedicated to a detailed description of the process of developing a working curriculum as a key element in ensuring the quality of the educational process in institutions of professional pre-higher education. It examines the main stages, pr